EDWARD MORGAN FORSTER AND HIS ASPECTS OF THE NOVEL - Ribut Surjowati (OKARA: Jurnal Bahasa dan Sastra, 2013)
Aspects of the Novel is the publication of a series of lectures on the English Language novel delivered by E.M. Forster. These lectures presents the seven aspects, Forster believes, should include in the novel. Those seven aspects are story, people, plot, fantasy and prophecy, pattern and rhythm. This article is elaborating those seven aspects along with the explanation. It is expected that after reading Forster’s lectures, people will get a better insight towards the form of a good novel.